Study of Cultural Clash in Mohsin Hamid’s The Reluctant Fundamentalist - Samina Bibi; Dr Abdul Waheed; Nijat Ullah Khan (Elementary Education Online, 2023)
This paper aims to explore the cultural clash in Mohsin Hamid’s The Reluctant Fundamentalist from postcolonial perspective. It investigates how the self and the other are at clash in the novel .It also examines how the cultural clash affects human psyche in the novel. The main objective of the paper is to explore the situation where cultural clash can be seen and how human psyche develop .The study is viewed under the vision of Edward Said’s Orientalism. The nature of the study is qualitative study which explores man’s constant struggles for cultural gratitude. The study also explores the issue of the self and the other, as it could be seen in the life cycle of Changez Khan how he suffered when he left his job .The study contributes the main stream of knowledge as it reveals the man’s psyche, in particular the one who is in power